A hybrid epitaxy method for InAs on GaP - Chen, A; Yulius, Aristo; Woodall, J M; Broadbridge, Christine (Applied Physics Letters, 2004)
The interface formation mechanism during the molecular-beam epitaxy (MBE) of InAs/GaP has been studied with the aid of the In-Ga-P phase diagram. It is discovered that an initial dissolution and crystallization process similar to liquid phase epitaxy (LPE) may happen at sufficiently high temperature, resulting in a graded composition at the interface. Consequently, "parasitic LPE/MBE" is the name for this hybrid form of MBE. High-resolution TEM images confirm the existence of the interfacial layer in the sample grown at high temperature. The graded interface smears out the band offset and leads to a nonrectifying heterojunction. Low-temperature (LT) MBE growth can turn off the LPE component, enabling the growth of an abrupt interface. Based on this "LPE/MBE" model, a LT MBE technique is developed to grow an abrupt InAs/InGaP interface for heterojunction power Schottky rectifiers. The LT InAs/InGaP heterojunction demonstrates nearly ideal Schottky rectifier characteristics, while the sample grown at high temperature shows resistive ohmic characteristics. The LT InAs/InGaP Schottky diode also demonstrates good stability with respect to anneal temperature, similar to the InAs/GaP heterojunctions. © 2004 American Institute of Physics.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-537-776-623-144 tex.type: [object Object]
Keywords: Baliga figure of merit (BFOM); Current voltage characteristics; Liquid phase epitaxy; Metal-semiconductor (MS) diodes; Molecular beam epitaxy; Phase diagrams; Rapid thermal annealer (RTA); Rapid thermal annealing; Schottkey rectifiers; Schottky barrier diodes; Semiconducting gallium compounds; Semiconducting indium compounds; Transmission electron microscopy; dept.phy

Vapor-liquid-solid growth of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition - Su, J; Gherasimova, M; Cui, G; Han, J; Lim, Sangyun; Ciuparu, Dragos; Pfefferle, Lisa D; He, Y; Nurmikko, A V; Broadbridge, Christine; Lehman, Ann Hein; Onuma, T; et al. (MRS Proceedings, 2004)
We report flexible synthesis of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Indium is used as an in-situ catalyst to facilitate and sustain the stability of liquid phase droplet for VLS growth based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst droplets and to promote nucleation statistics. Cathodoluminescence (CL) of GaN nanowires shows near band-edge emission at 370nm, and strong E 2 phonon peak is observed at room temperature in Raman scattering spectra. Both binary GaN and AlN nanowires have been synthesized by MOCVD. Three-dimensional AlN/GaN trunk-branch nanostructures are reported to illustrate the versatility of incorporating the VLS mechanism into MOCVD process. © 2005 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-591-869-918-808 tex.type: [object Object]
Keywords: Catalysis; Heterojunctions; Metallorganic chemical vapor deposition; Molecular beam epitaxy; Nanoelectronics; Nanostructured materials; Nanowires; Nucleation; Optical characterization; Synthesis (chemical); Thermodynamics; Vapor-liquid-solid (VLS) growth; dept.phy